Penentuan Awal Puasa Ramadhan dalam Perspektif Hadis - Lisa Istianah (Jurnal Riset Agama, 2021)
The purpose of this study is to discuss the hadith about fasting. This research method uses qualitative research through literature study with content analysis. The results and discussion of this study include general views of fasting, hadiths about fasting, and determining the beginning of Ramadan fasting. The conclusion of this study is that the hadith about fasting is found in various books, including Sunan an-Nasa'i, Sahih Muslim, Sunan Abu Dawud, Sunan Ibn Majah, and Jami 'at-Tirmidhi. Determining the start of Ramadan fasting can be done in two ways, namely the rukyat method and the reckoning method.